Strategi Penerapan Standar Nasional Indonesia Biskuit (SNI 2973:2011) bagi Industri Kecil Menengah - Syaiful, .; Hardjomidjojo, Hartrisari; Cahyadi, Eko Ruddy (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2018)
BSN on December 22, 2011 has stipulated SNI 2973: 2011 Biscuit through the Decree of the Head of BSN No.242/KEP/BSN/12/2011, scope of products in SNI 2973: 2011 are Biscuits, Krekers, Wafers and Pies, Kukis. Until now the number of industries that apply SNI Biscuits is still low from 595 brands of biscuit products that have been registered in BPOM (BPOM, 2017) only 28 brands of biscuits that have received the certificate of SNI (BSN, 2018). Developing strategies to apply SNI Biscuit for SME is to increase applying SNI, as well as input to related technical institution  and related party in conducting coaching related to application SNI products for SME. The results of the assessment of the readiness of the five SME in implementing SNI 2973: 2011 Biscuits respectively as follows: SME A is 97.4%; SME B is 84.5%; SME C of 83.6%; SME D of 62.9%; and SME E of 71.4%. The grouping of the five SME using statistical analysis four SME groups based on their level of readiness in applying Biscuit SNI, namely the first group that is ready to apply the Biscuit SNI (SME A) which is in zone 1; the two groups are quite ready in applying the Biscuit SNI (SME B and C) in zone 2; the three groups of SME that are less prepared in applying the Biscuit SNI (SME E) which are in zone 3; the four groups of SME that are not ready to apply the Biscuit SNI (SME D) which are in zone 4. The recommended strategy for the four groups of IKM using Ishikawa diagram which focuses on the lowest internal and external factors of resources in each SME group.